PROVERBIALITY IN THE REFORMATION CHRONICLE BY JOHANNES SALAT (1498–1561) - Frech, Stephan (Proverbium - Yearbook, 2023)
The chronicle of the Lucerne court clerk Johannes Salat describes the beginnings of the Swiss Reformation from a Catholic perspective. Through the wisdom attributed to proverbs, Salat places the events in a pre-structured interpretive context and remains impartial as a chronicler. The study aims to show the use of proverbs in their concrete manifestations: Mostly they are integrated into the text as proverbial sayings or phrasemes and therefore require syntactic adaptation. In order to adapt them to the context, their content is modified and often supplemented. Examples such as the Wolf im Schafspelz will be used to illustrate the linguistic tropes, in which proverbs and phrasemes can be recognised, with which the chronicler warns of the dangers that emanate from the teachings of Luther and Zwingli from an Old Faith perspective: Temptation, destruction and chaos.